PERTUMBUHAN TANAMAN MUDA SENGON UMUR 8 BULAN PADA BERBAGAI UKURAN LUBANG TANAM DAN DOSIS PUPUK KANDANG - Prijono, Agus (Jurnal Wana Tropika, 2019)
One of main supplier on wood industry is Sengon from private forestland. Sengon can be harvested at 5 years. Sengon has been planted in various areas, one of them in Widodomartani, Ngemplak , Sleman, Yogyakarta Province. The succes silviculture sengon if from planting to harvesting with good practice. One of supported succes planting is used depht holes and basic fertilizer. This research aims to determine the growth at eight month plants on some planting depth holes and compost dosis. Planting is done with a distance of 2 x 2 m in the planting hole measuring control, long and wide with same each 30 cm, 40 cm, and 50 cm . The planting hole each used 2 kg and 3 kg compost. The growth data (height and diameter) was taken in each treatment (7 treatments) and each treatment by three repeated. The data obtained were analyzed by Anova and if there were significant differences in the factors, followed by the UJGD test. The analysis showed that the treatment is significantly affect to the height and diameter growth. The growth rate of Sengon at 8th months planted is plant height 266,86 cm and 24,70 mm diameter. The planting holes 40 cm x 40 cm x 40 cm and 2 kg compost giving optimal result. The best growth of Sengon treatment is planting holes 50 cm x 50 cm x 50 cm and 2 kg compost with plant height 336 cm and 30,6 mm diameter at the 8th months plants. Keywords: Growth, Sengon, 8th months, planting hole, compost